Penafsiran Luas Bidang Dasar Tegakan Pinus Merkusii menggunakan Foto Udara di Kesatuan Pemangkuan Hutan (KPH) Kedu Perum Perhutani Unit 1 Jawa Tengah - Sahid, S (Forum Geografi, 2009)
The research aim to estimate the basal area of Pinus merkusii combired comprises measurement by aerial photograph with scale of 1:20.000 field and to measurement field. The stand parameters measured are the number of the trees per hectare (N), the tree height (H) and crown diameter (D). Whereas, estimation of the stand basal area was based on the measurement of the stem diameter in the permanent plots. The result of the regression analysis showed that the based area of the Pinus merkusii stand (lbds) had correlation with the number of the trees per hectare (N), the tree height (H) and crown diameter (D), the regression is as follows: Basal areas or tree densities of compartement 100 and 102 have been optimum. Therefore, resin production compartement 100 and 102 is higher than compartement 101 having lower basal are or tree density. It is for those reasons, the compartement 101 needs action to cut the suppressed trees to make optimum basal area.